Reaction of [18F]Fluoride at Heteroatoms and Metals for Imaging of Peptides and Proteins by Positron Emission Tomography - Scroggie, Kymberley R.; Perkins, Michael V.; Chalker, Justin M. (Frontiers in Chemistry, 2021)
The ability to radiolabel proteins with [18F]fluoride enables the use of positron emission tomography (PET) for the early detection, staging, and diagnosis of disease. The direct fluorination of native proteins through C F bond formation is, however, a difficult task. The aqueous environments required by proteins severely hampers fluorination yields while the dry, organic solvents that promote nucleophilic fluorination can denature proteins. To circumvent these issues, indirect fluorination methods making use of prosthetic groups that are first fluorinated and then conjugated to a protein have become commonplace. But, when it comes to the radio fluorination of proteins, these indirect methods are not always suited to the short half life of the fluorine-18 radionuclide (110 minutes). This review explores radiofluorination through bond formation with fluoride at boron, metal complexes, silicon, phosphorus and sulfur. The potential for these techniques to be used for the direct, aqueous radiolabeling of proteins with [18F]fluoride is discussed.